Case report: First autochthonous Babesia vulpes infection in a dog from Italy - Antognoni, Maria Teresa; Cremonini, Valentina; Misia, Ambra Lisa; Gobbo, Federica; Toniolo, Federica; Miglio, Arianna (Frontiers in Veterinary Science, 2025)
A 10-month-old intact female Cane Corso dog was referred to the Veterinary Teaching Hospital of the University of Perugia (PG-VTH) for severe hemolytic anemia and thrombocytopenia. The dog had never traveled abroad and was regularly treated with antiparasitic products. On physical examination, the dog showed lethargy, delayed growth, weight loss, pale mucous membranes, and abdominal pain. The temperature was normal, and on examination, no ectoparasites were observed on the animal’s body surface. The main laboratory findings were hemolytic anemia, thrombocytopenia, and elevated liver enzymes. Babesia infection was initially diagnosed by blood smear evaluation via May–Grünwald–Giemsa staining and then confirmed by real-time polymerase chain reaction analysis; further sequencing analysis attributed the infection to Babesia vulpes (B. vulpes). An initial treatment with imidocarb dipropionate was only partially effective, while resolution of the infection was reached afterward with a combination of Malarone® and azithromycin therapy. To the authors’ knowledge, this report describes the first case of B. vulpes infection in a dog in Italy.